Akebia quinata (Houtt.) Dcne., nova vrsta v slovenski flori, ter prispevek k poznavanju neofitske flore Primorske - Glasnović, Peter (Hladnikia (Ljubljana), 2010)
The article discusses Akebia quinata, a new alien species for the Slovenian flora. The authors provide a description of the species and its locality, and discuss its invasive potential, as in 2008, the species was recognized by the European and Mediterranean Plant Protection Organization as emerging invader in Europe. The authors also discuss the occurrence of several other neophytes in the Primorska region (Slovenia): Amaranthus deflexus, Artemisia annua, Aster squamatus, Bidens pilosa, Bidens subalternans, Broussonetia papyrifera, Pistia stratiotes and Senecio inaequidens.
Keywords: Akebia quinata; fitogeografija; flora; Goriška; Slovenian Istria; Slovenska Istra; tujerodne vrste